Integrating Multi-Omics, Bioinformatics and Genome Editing for Sustainable Sericulture - , Sumalini Bora, Prety Rekha Narzary, Manasee Hazarika Ahmed, Priyangana Chetia, Akash Neog Thengal (Archives of Current Research International, 2025)
Sericulture, centred on the mulberry silkworm Bombyx mori, is a millennia-old agro-based industry now facing challenges from climate variability, pathogen outbreaks, and the limitations of conventional breeding. Recent advances in molecular biology have revolutionised silkworm research, offering precision tools for genetic improvement and sustainable silk production. This review synthesises progress across three interconnected domains: multi-omics, bioinformatics, and genome editing. Genomic, transcriptomic, proteomic, and metabolomic studies have provided system-level insights into silk gland biology, immune responses, stress tolerance, and dietary adaptation. Specialised bioinformatics platforms such as SilkDB, KAIKObase, and MorusDB enable integration of diverse datasets, facilitating gene discovery, trait prediction, and marker-assisted breeding. Concurrently, genome editing technologies—particularly CRISPR/Cas9—have transformed functional genomics and trait engineering, enabling targeted improvements in silk yield, fibre quality, disease resistance, and climate resilience. Emerging tools such as base and prime editors further expand the potential for precise genetic manipulation. By linking omics-driven target identification, bioinformatics-guided prioritisation, and genome editing–based validation, sericulture is entering a new era of precision breeding. This integrative framework accelerates the development of resilient, high-yielding silkworm strains but also broadens applications in biomaterials, pharmaceuticals, and sustainable agro-industrial systems. Together, these innovations position sericulture as a modern bioindustry capable of meeting global demands while preserving rural livelihoods and ecological balance.